Critical assessment of health disparities across subpopulation groups through a social determinants of health perspective: The case of type 2 diabetes patients. (3rd April 2018) - Kim, Yong-Mi; Delen, Dursun
ABSTRACT: Background : Studies on diabetes have shown that population subgroups have varying rates of medical events and related procedures; however, existing studies have investigated either medical events or procedures, and hence, it is unknown whether disparities exist between medical events and procedures. Purpose : The objective of this study is to investigate how diabetes-related medical events and procedures are different across population subgroups through a social determinants of health (SDH) perspective. Methods : Because the purpose of this manuscript is to explore whether statistically significant health disparities exist across population subgroups regarding diabetes patients' medical events and procedures, group difference test methods were employed. Diabetes patients' data were drawn from the Cerner Health Facts® data warehouse. Results : The study revealed systematic disparities across population subgroups regarding medical events and procedures. The most significant disparities were connected with smoking status, alcohol use, type of insurance, age, marital status, and gender. Conclusions : Some population subgroups have higher rates of medical events and yet receive lower rates of treatments, and such disparities are systematic. Socially constructed behaviors and structurally discriminating public policies in part contribute to such systematic health disparities across population subgroups.